THE PORTRAYAL OF WOMEN’S AMBITIONS THROUGH THE CHARACTER OF NINA SAYERS IN BLACK SWAN - Aurel Pinkan Millenia; Agustin Diana Wardaningsih (Linguistics and Literature Students' Journal, 2023)
Ambition is the energy expressed in active behaviour towards a goal or aspiration, carried out with persistence and a common struggle in the pursuit of success, achievement, and completion. The existence of different societal perspectives related to men's and women's ambitions raises negative stigmas that harm women. Therefore, film is present as an entertainment medium, and as a channel to convey messages to portray social reality, and to change the perspective. One of the films that depict women's ambitions is "Black Swan" (2010) with the background of the main character who wants to achieve success in the ballet industry in a performance called "Swan Lake".This film highlights the struggles and sacrifices of Nina Sayers in her effort to get the main dancer position, with the pressures and obstacles she faced to reach the pinnacle of success. This study aims to determine the portrayal of women's ambitions through the character of Nina Sayers in "Black Swan". This research uses a qualitative approach, with semiotic analysis methods according to Christian Metz, through scenes that are categorized as depicting striving ambitions, perfectionist ambitions, and aggressive ambitions of Nina Sayers in "Black Swan"."Black Swan" gives a complex picture of women trying to achieve success in the competitive ballet industry. The portrayal of strong women's ambition and perseverance to achieve success in this film provides a point of view rarely explored in the film's narrative. Nina Sayers’ perfectionist personality shown most strongly in the film, "Black Swan" exemplifies that ambition and hard work know no gender boundaries. The film shows that women can also strive for success in their careers and are ready to make sacrifices to achieve those goals, just as men are.Keywords: Christian Metz, film, film semiology, the large syntagmatic category, women’s ambition